Development Of Psychological Preparation of Future Teachers on The Basis of Professional Reflection - Zarmasov Sherzod Rahimberdiyevich (Open Academia, 2024)
This article describes the importance of reflection in the development of professional pedagogical training of future teachers, the theoretical views of future teachers on self-confidence, increasing the need for pedagogical activity, the formation of creative motivation.
Keywords: reflection; professional pedagogical training; self-confidence